Proceedings of the Proceedings of the 7th Mathematics, Science, and Computer Science Education International Seminar, MSCEIS 20 2020
DOI: 10.4108/eai.12-10-2019.2296468
|View full text |Cite
|
Sign up to set email alerts
|

Development of Engage, Research, and Present (ERP) Instructional Model to Promote HOTs and 21st Century Moral Values: A Fuzzy Delphy Method

Abstract: Higher order thinking skill (HOTs) and 21stcentury moral values are pivotal skills to be mastered by college students in todays' digitalized era. This study,therefore aims to develop am an instructional model called Engage, Research, and Present (ERP) model. This provides opportunities for college students owning HOTs and 21st moral values. The Fuzzy Delphi Method (FDM) was employed to determine consensus among a panel of several experts. They come from educational and psychological experts (i.e. researchers) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The cases given in the case-based learning model using the ERP model are carried out in the phase engage, where the first stage is reading the phenomenon or in this case the case given by the educator. The ERP model aims to strengthen students' research abilities because it consists of several sub-phases that highlight research skills (Haryati et al, 2020), so that students can solve cases well. Each sub-phase in this model invites students to be involved in all activities that lead to how to solve cases scientifically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cases given in the case-based learning model using the ERP model are carried out in the phase engage, where the first stage is reading the phenomenon or in this case the case given by the educator. The ERP model aims to strengthen students' research abilities because it consists of several sub-phases that highlight research skills (Haryati et al, 2020), so that students can solve cases well. Each sub-phase in this model invites students to be involved in all activities that lead to how to solve cases scientifically.…”
Section: Discussionmentioning
confidence: 99%
“…In the engage phase, students are given cases that must be solved. In more detail the subphases on the ERP model syntax (Haryati et al, 2020) shown in table 2.…”
Section: Classroom Interventionmentioning
confidence: 99%
See 1 more Smart Citation